The Role of School Principals in Improving the Success of Elementary School Management: A Qualitative Case Study in Yogyakarta - Salim, Ahmad; Fuadi, Akhsanul; Rochaendi, Endi; Badriah, Laelatul (LP. Ma'arif Janggan Magetan, 2024)
The persistent challenges facing elementary education in Indonesia—ranging from inadequacies in curriculum design and instructional delivery to inefficiencies in resource management—necessitate transformative school leadership. This study critically investigates the strategic role of principals in improving educational quality through the integrated implementation of seven core leadership functions: as educator, manager, administrator, supervisor, leader, innovator, and motivator. Employing a qualitative case study design in Kasihan District, Bantul Regency, data were obtained through in-depth interviews, direct observations, and document analysis. The findings indicate that effective principals drive curricular relevance and innovation, foster collaborative pedagogical planning, and promote the integration of educational technologies. Moreover, they facilitate continuous professional development, ensure transparent and efficient resource utilization, and nurture strong community engagement. The study concludes that school principals act as pivotal agents in cultivating adaptive, inclusive, and innovation-oriented learning environments. It recommends capacity-building programs for school leaders and teachers, enhanced governance mechanisms, and strengthened stakeholder partnerships. These insights contribute to both the practical discourse on educational leadership development and the broader theoretical understanding of strategic school governance within decentralized educational systems.